Pengembangan Media Pembelajaran Video Animasi Interaktif Berbantuan Aplikasi Canva Pada Pelajaran IPAS Materi Norma Dalam Adat Istiadat Daerahku di Kelas IV Sekolah Dasar Negeri 108306 Tanjung Garbus: Research And Development - Lubis, Muhammad Rayhan; Darwis, Umar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine: 1). the validity of interactive animation video learning media assisted by the Canva application in improving student learning outcomes in the Natural Sciences lesson on norms in my regional customs. 2). the effectiveness of interactive animation video learning media assisted by the Canva application in improving student learning outcomes. 3). the practicality by teachers of interactive animation video learning media assisted by the Canva application was carried out in improving student learning outcomes. The method used in this study is the Research and Development (R&D) development method using the ADDIE model through five stages including: Analysis, Design, Development, Implementation, Evaluation. The subjects tested consisted of 13 fourth grade students. The results obtained from several relevant expert validators, namely media, material and practicality questionnaire experts obtained a feasibility score of 100%, media experts obtained a feasibility score of 93.3%, material experts obtained a feasibility score of 90%, teacher responses obtained a feasibility score of 96.6%, and student responses obtained a feasibility score of 96.6%. After the implementation of interactive learning media, there was an increase in student scores that met the criteria (KKM), from 4 students at the time of the pretest showing an increase to 9 students who met (KKM) in the posttest. However, when calculated using N-Gain, it showed a learning outcome of 0.29 which is classified as a low category. The results of the effectiveness test also showed that it had not provided a significant increase in student learning outcomes. Interactive animated video learning media assisted by Canva was declared very feasible to use, but its effectiveness still depends on the duration of application and the number of research subjects.